Investigating Rijndael-Based Algorithms for Audio Ciphering - Mohammed, Sajaa G.; Al-Mothafar, Nuhad Salim (Iraqi Journal of Science, 2025)
Voice encryption is crucial to protecting data during transmission and storage due to the widespread problem of document fabrication and forgery. Various methods have been used to protect important data, including encryption. Voice data encryption is a way to encrypt important messages within transmissions. Therefore, it needs a strong and efficient encryption algorithm, using the standard encryption algorithm known as Rijndeal. This method is reliable, secure and efficient, because the Rijndael algorithm is characterized by its key lengths and blocks of different sizes. The Rijndael algorithm is a method of decrypting audio files, making it a powerful tool for protecting sensitive information. This paper presents a method for encoding WAV audio files using the Rijndael algorithm that is compatible with many audio formats. This study converts audio data into a 256-bit audio sample that has been used to encode using the Rijndael algorithm, as this algorithm is known for its robustness and has won many awards. The working principle of this algorithm is to create multiple blocks with different sizes and keys (128 bits, 192 bits or 256 bits). The algorithm creates keys for the purpose of encryption, and they are combined into the audio files using the Rijndael algorithm and decrypted that has been noted as the return of the original text. The goal of this proposed methodology is to protect audio data from attacking people and reduce the chances of this data being disclosed. This methodology is used for the purpose of transferring, storing and keeping confidential audio files securely with security aspects. One of the most important features of this research is the strength of the encryption, which is represented by the Rigndael algorithm, which led to the file being broken and restored at a record rate of up to 100%. It also provides a cutting-edge and innovative methodology. For the purpose of securing, transmitting, storing and protecting audio data in all modern digital fields.